Determination of the pH and the free alkali metal content in the pore solution of concrete: Review and experimental comparison. (June 2017) - Plusquellec, G.; Geiker, M.R.; Lindgård, J.; Duchesne, J.; Fournier, B.; De Weerdt, K.
Abstract: The durability of concrete is affected by the pH of its pore solution, which is linked to the free alkali metal content. This paper starts with a literature review of methods for determining the pH and/or the free alkali metal content in the pore solution of concrete. Promising methods are compared in the second part of the paper. We then report on pore water expression (PWE) and three ex situ leaching methods (ESL) applied to Portland cement (CEM I) and Portland fly ash cement (CEM II/B-V) mortars. Finally, we make recommendations for the determination of the pH and the free alkali metal content of concrete. Because the measurement of the free-water content of the sample was found to be an important parameter, it is recommended to determine the pH with PWE and the free alkali metal content with ESL.